North central London elective orthopaedic network and health service innovation to improve the quality of NHS patient care. (2nd July 2021) - Thompson, Joshua W.; O'Brien, Alice; Stewart, Anna; Hurd, Rob; Haddad, Fares S
Abstract : Health service innovation is required to meet the ever-growing demands of modern medicine. This editorial discusses the transformation of the north central London elective orthopaedic network and the essential principles which future integrated care systems could incorporate.